RFID as Automatic Billing System on Smart Cart Based on Wireless Sensor Network at Clothing Store - Aulia, Hillyatul; kusumawardani, Mila; Rakhmania, Amalia Eka (Jurnal Jaringan Telekomunikasi, 2023)
The current billing system can only be done at the cashier by relying on human resources. So that it can increase the number of queues when consumers increase and purchase more than one product. Longer queues can waste time and energy so that it can reduce customer satisfaction. The billing process that can only be done at the cashier can also be an obstacle for customers in knowing the total bill when shopping. This can trigger an over budget so that customers have to increase their expenses. This research proposes an automatic billing system on a smart cart that can support the billing process, especially reading the total bill in real time. This system uses a Radio Frequency Identification (RFID) passive label attached to each product as a unique identification code. In the shopping cart there is an RFID reader that functions to read the label. The products that have been added to the cart will be displayed on the application intended for customers and the web server for the cashier. Information on the website includes product name, price per product unit, product quantity, and total bill.